Cultural memory of glory of the imperium Melayu at Pulau Penyengat: An exploration of Contrapuntal Sociology - Niko, Nikodemus; Casiavera, Casiavera; Wahyudi, Herry; Eka Saputra, Alfian; Qurdiansyah, Adhitya; Caroline, Afrina (Trigin Publisher, 2024)
This research serves as a reminder of the glory of the ancient Malay kingdom of Riau. The presence of Pulau Penyengat is strategic due to the strong cultural memories of the local community. Consequently, the island stands as a witness to the historical triumphs of the Malay kingdom of Riau. The study presents memories and cultural recollections on Pulau Penyengat. The method employed in exploring these cultural memories is contrapuntal sociology exploratory. The media used for data collection is a digital camera. Data presentation includes recent photos of historical sites on Pulau Penyengat. The research data sources consist of field data and exploratory literature data relevant to the theme of this research. The findings of this research identify the persistent cultural memory of the Malay empire on Pulau Penyengat as an advantage for tourism in the region. Furthermore, the parts of the kingdom that remain intact at the historical site serve as strong reminders of the ancient Malay kingdom that still linger in the memory of the people of Pulau Penyengat.